(3GdeaUd aj UfYI GdEYQGHs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3Gddg CMeO Ydi Cf LYdfi ef YdeGA GdYQHjI hdYd GdPjf jZVhf ef GdYQHjI hjVYhf ef ebOGQgG hjQjOhf Gf jNaVhG eG QaY Gddg ef efGQgG s
(3BNQgG (B:s
(3hGPG cGfhG eef jMPahf eY GdGOZGe ai jJSY hjJbi age eY YOe GecGfg GMPa Je GdcJGH HMeO Gddg s
(3GdUaMI GdChdi MOjKI hQbkG hcJGHIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs